Environmental Carrying Capacity Assessment—the Policy Instrument and Tool for Sustainable Spatial Management - Świąder, Małgorzata; Szewrański, Szymon; Kazak, Jan Krzysztof (Frontiers in Environmental Science, 2020)
Nowadays, we are facing a global change associated with the rapid population growth and natural resources demand, which impacts are accumulated in space and during the time. Therefore, humanity could be identified as Planet’s Ecological Bigfoot. The anthropopressure disturbed the natural Earth's regulatory capacity, which could be noticed by the unavailability of freshwater, irregularly temperatures, or interrupted biogeochemical flows. Moreover, the growth of population is expected, as well as the sprawl of urbanized areas, increasing demand for living space, food and humans Ecological Footprint. Therefore, the aim of the study was the implementation of the environmental carrying capacity (ECC) approach for more sustainable spatial management, especially in the context of developing residential areas in the city-region. The research evaluates the spatial policy established by the municipalities of the city and its surroundings and presents alternative scenarios of residential areas development. The alternative scenarios were built using excluded and restricted environmental zones to protect productive ecosystems. The impact of residential areas designed in spatial documents and scenarios has been assessed using the carbon footprint (CF) and biocapacity (BC) indicators within the environmental carrying capacity (ECC) framework. The lifestyle archetypes of the city's residents and its suburban zone were used as the main input for the assessment of CF and the natural areas required to assimilate human consumption. The comparison of CF and BC allowed verifying the consumed versus available resources and to quantify the state of the environment. First of all, the research indicated the potential areas for the future development of human settlements. Secondly, the potential number of inhabitants in residential areas was assessed. Furthermore, the impact of inhabitants was quantified using the ECC approach. Finally, the surface of natural areas required for CF assimilation was assessed. The proposed approach could be relevant for spatial management, spatial policy evaluation and modeling. It could provide a management tool and policy instrument for the sustainable development of human settlements. Moreover, it proposes implementation of environmental zones for allocation of land-use for housing purpose in a more sustainable manner, which is currently not used within the ECC assessment.